Thermal conductivity and mechanical properties of pitch-based carbon fibre reinforced aluminium composites fabricated by squeeze casting. (2nd January 2018) - Asano, Kazunori
Abstract: Pure aluminium and high-silicon aluminium alloy were reinforced with the discontinuous pitch-based carbon fibres by squeeze casting, then the thermal conductivity and the mechanical properties of the composites were investigated. Optical microscopy revealed that the fibres were in a random planar arrangement, and the transmission electron microscopy revealed that there is no interfacial reaction between the matrices and the fibres. The random planar arrangement of the fibres leads to the anisotropy of the composite. The fibre-reinforcement increased the thermal conductivity in the parallel direction for both pure aluminium and its alloy matrices, while the thermal conductivity decreased in the vertical direction. The increase in the elastic modulus by the reinforcement was not observed for both matrices. The proof stress of the pure aluminium increased by the reinforcement especially in the parallel direction, while that of the high-silicon alloy decreased by the reinforcement.